PENGARUH IMPREGNASI KOH PADA KATALIS BENTONIT BOJONG MANIK LEBAK BANTEN DALAM SINTESIS BIODIESEL DARI MINYAK JELANTAH - Muhammad Triyogo Adiwibowo; Meri Yulvianti; Agus Rochmat; Ali Faozin; M. Abdurahman Aziz; Sartika Arbantini; Rudi Hartono (JURNAL INTEGRASI PROSES, 2022)
Biodiesel is an alternative fuel from renewable resources that is more environmentally friendly. This study aimed to obtain the optimum conditions for making biodiesel from used cooking oil based on the percentage of NaOH impregnation on bentonite catalysts from Bojong Manik Lebak Banten. The biodiesel synthesis method used is base transesterification. The impregnation process prepared bentonite as a catalyst at variations of %KOH, namely 20, 26, 31, and 35% (w/w). The biodiesel reaction was carried out at a temperature of 60°C and a reaction time of 3 hours using a 3% catalyst for the amount of used cooking oil. The results were obtained at optimum conditions on a catalyst of 26% KOH (w/w) with a biodiesel yield of 91.2%, density of 0.870 g/mL, the viscosity of 4.1 cSt, the flash point of 129°C, and methyl ester content of 97.48%.